Sukan Malaysia 2022 / PM Dr Hoe Foo Terng - Hoe, Foo Terng (Academy of Language Studies, 2023)
Sukan Malaysia 2022 athletic events were held from 15 - 18 September 2022 at the Bukit Jalil National Stadium Kuala Lumpur. The 2022 SUKMA Games, officially known as the 20th SUKMA Games and commonly known as MSN 2022, was a multi-sport event that was originally scheduled to be held in Johor in July 2020. Due to COVID-19 and MCO, the event was postponed and later hosted by Kuala Lumpur. AP Dr. Hoe Foo Terng, a senior lecturer from the Mandarin Unit, Academy of Language Studies who is also a qualified national grade 1 track and field KOAM (Malaysia Amateur Athletic Union) technical officer since 2004